Social–Structural Antecedents Come Forward to Elicit Envy to Distant Out-Groups - Javakhishvili, Nino; Butsashvili, Nino; Vardanashvili, Irina; Gogibedashvili, Anna (Frontiers in Psychology, 2021)
This study utilizing correlation, regression, confirmatory factor analyses (CFAs), ANOVA, moderation and mediation analysis investigated connections of stereotypes, emotions, and sociocultural variables in a single-sample/single-group design. Prior to data processing, Georgian versions of the Stereotype Content Model (SCM) questionnaires were validated through CFA. The study looked at Georgian students' attitudes to: (a) representatives of German-speaking countries (87 participants) and (b) representatives of English-speaking countries (244 participants). Emotions predicted to these groups by social–structural antecedents—vitality and fear of assimilation—and stereotypes were admiration, pride, and sympathy. In addition, envy was predicted for the English-speaking group. The prediction of envy is explained by moderation analysis according to which it is elicited by the interplay of warmth and competence, as well as fear of assimilation and competence. The former interaction mediates the link between social–structural antecedents to emotions. Thus, distant out-groups elicit envy as a result of their perceived vitality, fear of assimilation, warmth, and competence. Social–structural antecedents come forward to elicit emotions of envy independently as well as in interaction with stereotypes when small country representatives evaluate representatives of the influential group of English-speaking people.